2009
DOI: 10.1007/s12640-009-9072-7
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Deficiency Reduces Neurogenesis Accompanied by Neuronal Apoptosis Through Caspase-Dependent and -Independent Signaling Pathways

Abstract: Dietary zinc deficiency may affect zinc homeostasis in the brain and lead to reductions of neurogenesis and neuronal survival. However, the mechanisms responsible for the effects of zinc deficiency on hippocampal neurogenesis and neuronal death remain obscure. In the present study, young CD-1 mice were fed with zinc-deficient diet (0.85 ppm) for 5 weeks. The vesicular zinc was reduced at CA1 and CA3 regions of the hippocampus in zinc-deficient mice. The significant decreased zinc ions was associated with a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 56 publications
5
53
0
1
Order By: Relevance
“…Previous studies have shown that low dietary Zn 2+ intake in rats and mice impairs neurite outgrowth in the brain (26,27). CREB activity and neurite outgrowth are closely linked phases of neuronal differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that low dietary Zn 2+ intake in rats and mice impairs neurite outgrowth in the brain (26,27). CREB activity and neurite outgrowth are closely linked phases of neuronal differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…In comparison to previous studies in adult brain, we found higher levels of zinc in cerebral organoids, although compatible in scale of dosage (Table 2). While higher concentrations of zinc in adult brain are toxic to neural cells and also cause axonal degeneration in mice (47), zinc modulates the proliferation of stem cells and neuronal differentiation during neurogenesis (31)(32)(33). In accordance, previous data from our group have demonstrated increased zinc during neural differentiation of human pluripotent stem cells (48), which may highlight the importance of zinc for the commitment of neural stem cells and justify why levels found in cerebral organoids are subtly higher than those described in the adult brain (Table 2) (9,49,50).…”
Section: Implications Of Trace Elements Detected In Cerebral Organoidmentioning
confidence: 99%
“…As the period of infancy is most susceptible to dietary zinc deficiency (Sandstead et al, 2000), in the present study, an animal model of maternal zinc deficiency during lactation was used to examine the changes in hippocampal neuronal apoptosis, and the neurotrophic signaling pathways. Previous works have shown that dietary zinc deficiency could cause reduction in hippocampal zinc levels in postnatal and adult rodent brains (Takeda, 2001;Gao et al, 2009). This supports the notion that a reduction in hippocampal zinc is involved in brain dysfunctions, at least partly, caused by neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%